Effect of multilayer coating on mechanical properties of Nicalon-fibre-reinforced silicon carbide composites - Kim, YW; Lee, JG; Kim, MS; Park, JH (CHAPMAN HALL LTD, 1996)
Nicalon-fibre-reinforced SiC composites were fabricated by combining polymer solution infiltration (PSI) and chemical vapour infiltration (CVI). Effect of multilayer coating on mechanical properties of the composites was investigated. The coatings consisted of chemically vapour deposited (CVD) C and SiC and were designed to enhance fibre pull-out in the composites. It was found that the flexural strength and fracture toughness of the composites were increased with the number of coating layers and was a maximum for 7 coating layers which consisted of C/SiC/C/SiC/C/SiC/C. Typical flexural strength and fracture toughness of the composites were 300 MPa and 14.5 MPa m(1/2), respectively.
Keywords: BRITTLE-MATRIX COMPOSITES; CERAMICS; STRENGTH